Effect of the solar wind on the nature of arbitrary amplitude ion-acoustic solitary waves in Venus' upper ionosphere. Issue 2 (11th October 2022) - Salem, S; Fayad, A A; El-Shafeay, N A; Sayed, F S H; Shihab, M; Fichtner, H; Lazar, M; Moslem, W M
ABSTRACT: Observations suggest that at altitudes of 1000–2000 km the interaction between the solar wind and Venus' ionospheric plasma leads to ion-acoustic waves (IAWs) formation. For studying this hypothesis, a suitable hydrodynamic model relying on the observational data from Pioneer Venus Orbiter ( PVO ) and Venus Express ( VEX ) is developed. It consists of two ionospheric fluids of positive ions, hydrogen (H + ), and oxygen (O + ), and isothermal ionospheric electrons interacting with streaming solar wind protons and isothermal solar wind electrons. The favourable conditions and propagation characteristics of the fully non-linear IAWs along with their dependence on solar wind parameters are examined and compared with the available space observations. It is found that the pulse amplitude is decreased by increasing the temperature of either the solar wind protons or electrons. In contrast, a higher relative density or velocity of the solar wind protons amplifies the amplitude of the solitary structures. Moreover, only velocity variations within a certain range called the plasma velocity scale can affect the basic features of the solitary pulses. Beyond this scale, solitary waves are not affected by the solar wind protons' velocity anymore. This theoretical model predicts the propagation of electrostatic solitary waves with a maximum electric field of 7.5 mV m −1 and a pulse time duration of 3 ms. The output of the fast Fourier transformation (FFT) power spectra of the electric field pulse is a broad-band electrostatic noise in a frequency range of ∼0.1–4 kHz. These FFT calculations are in good agreement with PVO's observations.